Association of Chlamydia trachomatis infection with cervical atypia in adolescent women with short-term or long-term use of oral contraceptives: a longitudinal study in HPV vaccinated women. Issue 6 (1st June 2022) - Adhikari, Indira; Eriksson, Tiina; Harjula, Katja; Hokkanen, Mari; Apter, Dan; Nieminen, Pekka; Luostarinen, Tapio; Lehtinen, Matti
Abstract : Objective: We assessed the relationship between Chlamydia trachomatis infection, duration of oral contraceptive (OC) use and cervical atypia among young adult Finnish women. Design: A longitudinal study. Setting and participants: Women who were included in this study participated in a community-randomised trial on the effectiveness of human papillomavirus (HPV) vaccination and C. trachomatis screening at ages 18.5 and 22 years in Finland. They completed questionnaires on both visits about sexual behaviours. The cytology test results at age 18.5 and 22 years were also available for those women. The total number of participants in this study at 18.5 years of age were 11 701 and at 22 years of age were 6618. Main outcome measure: ORs with 95% CIs using univariable and multivariable logistic regression were used to assess the association between C. trachomatis infection, duration of OC and squamous intraepithelial lesions (SIL). Results: There were 940 cytological SIL cases at the first screening visit and 129 cytological SIL cases at the second screening visit. Among the 22 years old, more than fourfold adjusted risk of SIL was associated with C. trachomatis positivity. The HPV16/18, condom use, smoking and number of sexual partners adjusted joint effect of prolonged OC use and C. trachomatis was significantly increased (OR 4.7, 95% CI 1.7 to 12.8) in the 22-year-old women. This observed joint effect was 1.6 times higher than expected on a multiplicative scale. On additive scale, the observed relative excess risk from interaction was 1.8. Conclusion: The risk of SIL in HPV vaccinated women is significantly increased if they are C. trachomatis positive and have used OC for 5 or more years. The biological basis may be lack of condom facilitated protection against sexually transmitted diseases. Trial registration number: NCT00534638 .